Integrating Pancasila Student Profile Values into Islamic Religious Education at Sekolah Penggerak - Anis Joko Santoso; Kasinyo Harto; Fitri Oviyanti (AL-ISHLAH: Jurnal Pendidikan, 2025)
The study evaluates the internalization of the Pancasila Student Profile values in Islamic Religious Education (IRE) learning in Ogan Komering Ilir Regency. It also examines the implications for students, identifying challenges in the internalization process. A mixed-methods approach with an Exploratory Sequential design was employed. The study involved all implementers of the first batch of the school program, with a sample of six schools. Data collection techniques included observations and interviews for qualitative data and surveys for quantitative data. Qualitative data were analyzed through direct interpretation, while quantitative data were processed using the Rasch model via the Jamovi application. Findings indicate that all six schools implemented various strategies to internalize the Pancasila Student Profile values. The degree of internalization varied, with the highest scores in faith and moral character and the lowest in creativity. Overall, 90.5% of the values were successfully internalized by students. The study highlights key challenges in value internalization, particularly in fostering "eliminating stereotypes and prejudices" and enhancing "flexibility of thinking in problem-solving". These findings suggest the need for more structured interventions to strengthen these aspects. While the internalization of Pancasila Student Profile values in IRE learning has been largely successful, improvements are needed in specific indicators. Addressing these challenges can further enhance students' character development and critical thinking skills.